Pendidikan Pendidikan Enterpreunersip Berbasis Pesantren di Pondok Pesantren Miftahul Ulum Panyeppen Pamekasan. - Abdullah, Moh; Salik, Mohammad; Muchlis, Muchlis (LP2M IAI Miftahul Ulum Pamekasan, 2023)
This article discusses the Islamic boarding school-based entrepreneurial education model. Preparing hard skills and competencies for prospective Islamic boarding school graduates, as a strategy so that they are not unemployed after graduating, encourages the Miftahul Ulum Panyeppen Islamic boarding school to design an Islamic boarding school-based entrepreneurial education model. The entrepreneurial education model is the focus of this article. The method used uses a qualitative method with a naturalistic phenomenological approach. The results of this research show that the impact of the entrepreneurial education model can equip students so that after graduating from the Islamic boarding school they have competence, resulting in no hassle looking for employment, because graduates who have entrepreneurial competence are recruited as employees working in the Islamic boarding school's business units, such as BMT. , KOIM etc This article discusses the Islamic boarding school-based entrepreneurial education model. Preparing hard skills and competen This article discusses the Islamic boarding school-based entrepreneurial education model. Preparing hard skills and competencies for prospective Islamic boarding school graduates, as a strategy so that they are not unemployed after graduating, encourages the Miftahul Ulum Panyeppen Islamic boarding school to design an Islamic boarding school-based entrepreneurial education model. The entrepreneurial education model is the focus of this article. The method used uses a qualitative method with a naturalistic phenomenological approach. The results of this research show that the impact of the entrepreneurial education model can equip students so that after graduating from the Islamic boarding school they have competence, resulting in no hassle looking for employment, because graduates who have entrepreneurial competence are recruited as employees working in the Islamic boarding school's business units, such as BMT. , KOIM etc This article discusses the Islamic boarding school-based entrepreneurial education model. Preparing hard skills and competencies for prospective Islamic boarding school graduates, as a strategy so that they are not unemployed after graduating, encourages the Miftahul Ulum Panyeppen Islamic boarding school to design an Islamic boarding school-based entrepreneurial education model. The entrepreneurial education model is the focus of this article. The method used uses a qualitative method with a naturalistic phenomenological approach. The results of this research show that the impact of the entrepreneurial education model can equip students so that after graduating from the Islamic boarding school they have competence, resulting in no hassle looking for employment, because graduates who have entrepreneurial competence are recruited as employees working in the Islamic boarding school's business units, such as BMT. , KOIM etc